An experimental study on the environmental impact of hydrogen and natural gas blend burning - Ozturk, Merve; Sorgulu, Fatih; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this study, an experimental investigation is conducted to analyze the effect of adding hydrogen into natural gas on emissions and the burning performance of the obtained blends. Natural gas alone and natural gas-hydrogen blends are burned in identical gas stoves, and the emitted CO, CO2, and NOx are measured. The base case with natural gas only is compared with the natural gas and hydrogen blends (including hydrogen additions of 10%, 20% and 30% volumetrically). The experimental results show that the combustion efficiency increases from 39.32% to 44.4% by enhancing the hydrogen blending ratio from 0 to 0.3. While CO2 and CO emissions are reduced with rising the hydrogen ratio in the blend, NOx emissions have a fluctuating trend. Moreover, a life cycle analysis is performed to determine the environmental impact of the considered blending scenarios. With the blending ratio of 0.3 hydrogen by volume, global warming potential decreases from 6.233 to 6.123 kg CO2 equivalents per kg blend, and acidification potential reduces from 0.0507 to 0.04928 kg SO2 equivalents per kg blend in comparison with natural gas. On the other hand, human toxicity, abiotic depletion, and ozone depletion potentials per kg blend show slight augmentation from 5.30 to 5.52 kg 1,4-dichlorobenzene (DCB) eq., 0.0000107 to 0.00005921 kg SB eq., and 3.17 x 10-8 to 5.38 x 10-8 kg CFC-11 eq., respectively.
Keywords: Environmental impact; Emissions; Hydrogen; Natural gas; Efficiency; Life cycle assessment; Environmental Sciences & Ecology